The Political Economy of Development: State–Market Relations and Global Capitalism in The Scholarly Literature - Muhammad Abrar; Muhammad Aris Muladi (JURNAL NAWALA POLITIKA, 2026)
The political economy of development is a significant field of inquiry that examines the interaction between political power and economic dynamics at the national and global levels. This study aims to map and analyze the development of the political economy of development literature, with a particular focus on state–market relations and global capitalism. The research employs a Systematic Literature Review (SLR) combined with bibliometric co-occurrence analysis of peer-reviewed journal articles published between 2000 and 2025. Bibliographic data were analyzed using VOSviewer to identify thematic clusters, conceptual linkages, and temporal research trends. The findings indicate that the political economy of development literature is structured around several core themes, including the role of the state and public institutions, global capitalism and economic globalization, and state–market relations in the formulation of development policies. The results further suggest that global capitalism shapes national policy spaces asymmetrically, leading state–market relations to be understood as a dynamic arena of negotiation rather than a binary opposition. Moreover, the growing use of bibliometric approaches reflects increasing methodological maturity and reflexivity within the field of political economy of development studies. This study contributes by providing a systematic mapping of the intellectual structure and research trajectories of the political economy of development, while offering a conceptual foundation for future research and the formulation of adaptive development policies in the context of global capitalist dynamics.